Assessment of Plant Growth in Aeroponic Systems Integrated with Smart Farming Compared to Conventional Methods - Ihsan, Muhammad; Elsi, Zulhipni Reno Saputra (JURNAL TEKNOLOGI DAN ILMU KOMPUTER PRIMA (JUTIKOMP), 2025)
The increasing demand for sustainable agriculture in Indonesia and challenges like land scarcity and inefficient resource use have driven interest in innovative farming technologies. This study investigates the comparative effectiveness of an innovative farming-based aeroponic system versus a conventional soil-based system in cultivating green chili. A quantitative experimental design was employed, using IoT-integrated sensors in the aeroponic setup to monitor and control environmental parameters, while the conventional system relied on manual practices. Key growth indicators, including plant height, number of leaves, and wet and dry weight, were measured over a 30-day day. Statistical analysis revealed that the aeroponic system significantly outperformed the conventional system across all parameters (p < 0.05), with dry weight showing the most substantial improvement. These findings underscore the potential of smart aeroponics in enhancing crop productivity and resource efficiency. However, cost, energy dependency, and scalability considerations must be addressed to enable broader adoption. The study contributes to the growing body of evidence supporting precision agriculture as a viable strategy for sustainable food production.